EVALUASI KETAHANAN KULTIVAR SORGUM TERHADAP PENYAKIT LAYU FUSARIUM - Asniah, Asniah; Gusnawaty, HS; Taufik, Muhammad (Jurnal Agroteknos, 2013)
This study aimed to evaluate the resistance of sorghum cultivars to wilt fusarium. This research was arranged in a randomized block design, with six  treatments [brown  sorghum, white sorghum and  red  sorghum with no inoculation fusarium, brown    sorghum, white sorghum  and  red  sorghum with  inoculation  fusarium]  with  3  (three)  replications. Data observed were plant height, leaf number, leaf area, and heaviest of grain weight for vegetative observation, while for disease character was disease incidence. The results showed that none of sorghum cultivars evaluated showed resistance to wilt fusarium infection. The tolerant response to wilt fusarium  was observed on brown sorghum, whereas red and white sorghum were  susceptible to wilt fusarium. The heaviest of  grain weight was found in brown sorghum (27.86 g/penicle). The wilt fusarium caused disease incidences ranging from 33.33% (brown sorghum)  to 50% (red sorghum). Keywords: cultivars, disease incidence, fusarium, sorghum, resistance